2007
DOI: 10.1128/aac.00294-06
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacodynamics of Meropenem in Patients with Lower Respiratory Tract Infections

Abstract: Studies of ␤-lactam pharmacodynamics in infected patients are sparse. In this study, classification and regression tree (CART) and logistic regression analyses were used to identify which pharmacodynamic indices and magnitudes were significant predictors of meropenem efficacy for 101 adult patients with lower respiratory tract infections (LRTI). Using demographic data, a validated population pharmacokinetic model was employed to predict pharmacokinetic parameters and free serum concentrations in the studied pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
188
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(198 citation statements)
references
References 18 publications
4
188
1
5
Order By: Relevance
“…For LZD, the determined value of 56 for f AUC/MIC in the present work is fairly close to the breakpoints in animals (AUC/MIC of 83)37 and humans (AUC/MIC of 51–85)38 for bloodstream infections if protein binding is considered. For MER, the determined value of 52% f %T >MIC was also in good agreement with the clinical breakpoint for microbiological response of 54% determined in patients with lower respiratory tract infections, in which S. aureus was the second‐most abundant pathogen 39. For VAN, the f AUC/MIC breakpoints from the clinical studies40, 41 tended to be fairly higher (125–400) than the calculated values (59–94) of the present work, which could originate from the partly impaired tissue distribution of VAN,42 whereas for MER and LZD, unbound plasma concentrations might be a fair predictor of tissue concentrations,43, 44, 45 if determined under appropriate analytic conditions 24, 46, 47.…”
Section: Discussionsupporting
confidence: 79%
“…For LZD, the determined value of 56 for f AUC/MIC in the present work is fairly close to the breakpoints in animals (AUC/MIC of 83)37 and humans (AUC/MIC of 51–85)38 for bloodstream infections if protein binding is considered. For MER, the determined value of 52% f %T >MIC was also in good agreement with the clinical breakpoint for microbiological response of 54% determined in patients with lower respiratory tract infections, in which S. aureus was the second‐most abundant pathogen 39. For VAN, the f AUC/MIC breakpoints from the clinical studies40, 41 tended to be fairly higher (125–400) than the calculated values (59–94) of the present work, which could originate from the partly impaired tissue distribution of VAN,42 whereas for MER and LZD, unbound plasma concentrations might be a fair predictor of tissue concentrations,43, 44, 45 if determined under appropriate analytic conditions 24, 46, 47.…”
Section: Discussionsupporting
confidence: 79%
“…This is further supported by studies that correlate optimised antibiotic exposure with improved patient outcome [6][7][8][9][10][11][12].…”
Section: Introductionsupporting
confidence: 52%
“…Dr. Roberts and colleagues suggested the use of trough concentrations as another PK-PD target at 4-5 × the concentration of the MIC for the pathogen and reported that the clinical success rate was 87.3% during beta-lactam TDM [25]. As observed by Dr. Roberts and colleagues, contrasting target values of %T > MIC were recently reported by some authors [26,27]. The very limited pertinent literature for beta-lactam TDM does not allow a direct comparison between our evaluation and those of previous trials; however, the results from the available reports and the present study are equivalent and suggest that beta-lactam TDM is useful to successfully personalize treatment.…”
Section: Dose Individualizationmentioning
confidence: 76%